Epigenetic reprogramming enhances the therapeutic efficacy of osteoblast‐derived extracellular vesicles to promote human bone marrow stem cell osteogenic differentiation. Issue 9 (7th July 2021) - Man, Kenny; Brunet, Mathieu Y.; Fernandez‐Rhodes, Maria; Williams, Soraya; Heaney, Liam M.; Gethings, Lee A.; Federici, Angelica; Davies, Owen G.; Hoey, David; Cox, Sophie C.
Abstract: Extracellular vesicles (EVs) are emerging in tissue engineering as promising acellular tools, circumventing many of the limitations associated with cell‐based therapies. Epigenetic regulation through histone deacetylase (HDAC) inhibition has been shown to increase differentiation capacity. Therefore, this study aimed to investigate the potential of augmenting osteoblast epigenetic functionality using the HDAC inhibitor Trichostatin A (TSA) to enhance the therapeutic efficacy of osteoblast‐derived EVs for bone regeneration. TSA was found to substantially alter osteoblast epigenetic function through reduced HDAC activity and increased histone acetylation. Treatment with TSA also significantly enhanced osteoblast alkaline phosphatase activity (1.35‐fold), collagen production (2.8‐fold) and calcium deposition (1.55‐fold) during osteogenic culture ( P ≤ 0.001). EVs derived from TSA‐treated osteoblasts (TSA‐EVs) exhibited reduced particle size (1‐05‐fold) ( P  > 0.05), concentration (1.4‐fold) ( P  > 0.05) and protein content (1.16‐fold) ( P ≤ 0.001) when compared to untreated EVs. TSA‐EVs significantly enhanced the proliferation (1.13‐fold) and migration (1.3‐fold) of human bone marrow stem cells (hBMSCs) when compared to untreated EVs ( P ≤ 0.05). Moreover, TSA‐EVs upregulated hBMSCs osteoblast‐related gene and protein expression (ALP, Col1a, BSP1 and OCN) when compared to cells cultured with untreated EVs. Importantly, TSA‐EVs elicited a time‐dose dependent increase in hBMSCs extracellular matrix mineralisation. MicroRNA profiling revealed a set of differentially expressed microRNAs from TSA‐EVs, which were osteogenic‐related. Target prediction demonstrated these microRNAs were involved in regulating pathways such as 'endocytosis' and 'Wnt signalling pathway'. Moreover, proteomics analysis identified the enrichment of proteins involved in transcriptional regulation within TSA‐EVs. Taken together, our findings suggest that altering osteoblasts' epigenome accelerates their mineralisation and promotes the osteoinductive potency of secreted EVs partly due to the delivery of pro‐osteogenic microRNAs and transcriptional regulating proteins. As such, for the first time we demonstrate the potential to harness epigenetic regulation as a novel engineering approach to enhance EVs therapeutic efficacy for bone repair. Abstract : Epigenetic regulation promotes the osteogenic potency of osteoblast‐derived EVs for bone repair. The HDAC inhibitor Trichostatin A (TSA) altered osteoblast epigenetic functionality through hyperacetylation, enhancing its mineralisation capacity. EVs derived from TSA treated osteoblasts (TSA‐EVs) were enriched with pro‐osteogenic microRNAs and transcriptional regulating proteins. TSA‐EVs significantly promoted hBMSCs osteogenic differentiation and mineralisation. Epigenetic reprogramming provides a novel engineering approach to enhance EVs therapeutic efficacy as an acellular tool for bone regeneration.